TEACHING READING RECOUNT TEXTS THROUGH TRI FOCUS STEVE SNYDER TECHNIQUE - Yus Vernandes Uzer (HOLISTICS, 2020)
The main problem of this study was “Was there any significant difference between the students who were taught reading recount texts through tri focus Steve Snyder to the tenth grade students of State Senior High School 12 Palembang and those who were not?”. This study applied a Quasi-Experimental design. The population in this study was all the tenth grade students and the sample consisted of 36 students which were taken by using purposive sampling. To analyze the data, the writer used independent sample t-test by using SPSS 23. The result of this study showed that the experimental group students’ average score in pre-test was 60.69, and in post-test it was 78.19 while the control group students’ average score in pre-test was 60.14 and in post-test was 68.68. From the t-test calculation, it was found that t-obtained value was 4.099 and the value of t-table was 1.994 with significance level 0.05 with df 70 for two tailed test. Since the t-obtained was higher than t-table, 4.099 > 1.994, it meant that the Null hypothesis (Ho) was rejected and Alternative hypothesis was accepted. It could be interpreted that there was a significant difference between the students who were taught reading recount texts through tri focus Steve Snyder to the tenth grade students of State Senior High School 12 Palembang and those who were not.